ECOLOGICAL IMPACT OF Merremia peltata (L.) Merrill INVASION ON PLANT DIVERSITY AT BUKIT BARISAN SELATAN NATIONAL PARK - Jani Master (BIOTROPIA, 2013)
Bukit Barisan Selatan National Park (BBSNP) is the third largest protected area in Sumatra.  Unfortunately, the area is invaded by Merremia peltata which occupied  about  7 000 ha. The aims of this study was to determine the ecological impacts of  M. peltata on plant biodiversity at BBSNP. Three locations were selected for vegetation analysis and M.peltata invasion assessment on the vegetation composition in BBSNP, i.e. the primary forest representing undisturbed area, secondary forest representing burned area, and invaded forest representing forest invaded by M. peltata. Three line transects  were constructed at each locations along1 km, and  the nested sampling plots were constructed every 100 m with the following quadrants : 20 m x 20 m for trees, 10 m  x 10 m for poles, 5 m  x 5 m for sapling, and 2 m x 2 m for seedling. The data collected were invasions of M. peltata, trees species, and diameter of the trees.  Invaded forest has lower diversity index (1.90)  than the other two. This caused by the invasion of M. peltata as the percentage of coverage in the invaded forest reached 44% compared to secondary and the primary forest which were  27.11% and 1.00%. It is evidenced by the correlation between the percentage of coverage M. peltata and diversity index (-0.988).